PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN, KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN (Studi Empiris Pada Rumah Makan Sate Bu Tris Banyuputih Batang) - Arif Rachman Hakim, 13.05.51.0220; Sutedjo, Bambang (Students' Journal of Economic and Management, 2018)
The research object was conducted at the Sate Bu Tris Restaurant in Banyuputih Batang. This study aims to find out and analyze the effect of price perception, product quality and service quality on consumer satisfaction of Sate Bu Tris Restaurant in Banyuputih Batang. Research samples were 100 respondents. The sampling technique is done by using purposive sampling, which is a sample determination technique with certain considerations. The criteria used in sampling with purposive sampling method are consumers who buy food and drinks at least 3 times at Sate Bu Tris Batang Restaurant. Data analysis method uses multiple regression. The results of testing the first hypothesis shows that partially (individuals) there is a positive and significant influence between Price Perception on consumer satisfaction; Partially (individuals) there is a positive and significant influence between Service Quality on consumer satisfaction and partially (individuals) there is a positive and significant influence between Product Quality on consumer satisfaction. Keywords: price perception, product quality, service quality and customer satisfaction